2018
DOI: 10.1177/0033294118792686
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Factor Structure of the Adolescent Stress Questionnaire in Chinese Adolescents

Abstract: This study evaluated the psychometric properties of the Chinese version of Adolescent Stress Questionnaire ( ASQ-CN) in a sample of Chinese middle school students ( N = 420; 52.14% boys and 47.86% girls). Iterated principal factor analysis and multiple-group principal components cluster analysis supported a six-factor model with 42 items out of 58 items in the ASQ-CN. The internal consistency was from .82 to .90. Girls reported lower stress levels in one subscale, Stress of romantic relationship, whereas no ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 127 publications
(159 reference statements)
1
2
0
Order By: Relevance
“…There are significant gender differences in stress symptoms of secondary school students, which is generally consistent with the findings of previous studies ( 37 , 38 ). The total score of stress symptoms and the scores of muscle tension and upper respiratory of girls were significantly higher than those of boys.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There are significant gender differences in stress symptoms of secondary school students, which is generally consistent with the findings of previous studies ( 37 , 38 ). The total score of stress symptoms and the scores of muscle tension and upper respiratory of girls were significantly higher than those of boys.…”
Section: Discussionsupporting
confidence: 91%
“…Compared with boys, in addition to the most obvious effect of punishment on depression, neurological, and cardiopulmonary arousal symptoms, relationship stress, adaptation, and learning stress events also had the most obvious effect on girls’ anger, sympathetic arousal, muscle tension, and upper respiratory. It is worth noting that since girls have higher empathy ability than boys and their overall relationships are better than boys ( 38 , 40 ), the stress generated to maintain good relationships is more likely to be an important source of stress symptoms. Therefore, the mechanism of influence of stress events on stress symptoms is different between boys and girls in secondary school.…”
Section: Discussionmentioning
confidence: 99%
“…Each participant rated the level of stress experienced on a 5-point likert scale (1 = not at all stressful to 5 = very stressful). The ASQ is widely regarded as a reliable and valid instrument in evaluating adolescent stressors from various sources [ 52 55 ]. In this study, the 10 subscales of ASQ showed excellent psychometric properties (α = 0.90–96).…”
Section: Methodsmentioning
confidence: 99%